2015
DOI: 10.1039/c5ra03848k
|View full text |Cite
|
Sign up to set email alerts
|

Substituted group directed assembly of zinc coordination compounds based on bifunctional ligands, from mono, di to tristetrazole–carboxylate

Abstract: Four new tetrazole–carboxylate ligands have been reacted with zinc salts, resulting in the formation of four compounds with enhanced luminescence properties and structures that are controlled by the number, different coordination modes and substitution of the ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…As shown in Figure 1, the Mn II ion lies on an inversion center and is six‐coordinate by two oxygen (O1, O1A) atoms from the carboxylate group of two pymtza ligands and four oxygen (O3, O3A, O4, O4A) atoms from four water molecules, forming a distorted MnO 6 octahedral arrangement. The Mn–O distances [2.1563–2.226(2) Å] are similar to those of previously reported Mn II complexes 21. Compared to the previously reported 2D complex [Mn(pztza) 2 (H 2 O) 2 ],9 in which the pztza ligand acts as a bidentate ligand bridging coordination mode by the pyrazinyl ring and the oxygen of the carboxylate group, the pymtza anion in 1 acts as a monodentate ligand to connect one Mn II ion by one carboxylate oxygen atom, resulting in a mononuclear structure.…”
Section: Resultssupporting
confidence: 86%
“…As shown in Figure 1, the Mn II ion lies on an inversion center and is six‐coordinate by two oxygen (O1, O1A) atoms from the carboxylate group of two pymtza ligands and four oxygen (O3, O3A, O4, O4A) atoms from four water molecules, forming a distorted MnO 6 octahedral arrangement. The Mn–O distances [2.1563–2.226(2) Å] are similar to those of previously reported Mn II complexes 21. Compared to the previously reported 2D complex [Mn(pztza) 2 (H 2 O) 2 ],9 in which the pztza ligand acts as a bidentate ligand bridging coordination mode by the pyrazinyl ring and the oxygen of the carboxylate group, the pymtza anion in 1 acts as a monodentate ligand to connect one Mn II ion by one carboxylate oxygen atom, resulting in a mononuclear structure.…”
Section: Resultssupporting
confidence: 86%
“…K4‐pytza ligand was prepared according to the literature . Other chemicals were commercially available reagents of analytical grade and were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…The ligands were prepared according to the literature methods [5,10]. Other chemicals were commercially available reagents of analytical grade used without further purification.…”
Section: Materials and Instrumentsmentioning
confidence: 99%
“…4 For some time now, we have been dedicated to the design and synthesis of coordination compounds based on tetrazole derivatives, where we found that the different substituted group may not only have a great impact on the rigidity and exibility of these ligands, thus leading to structure variation of such coordination compounds, but also inuence their physical and chemical properties. 5 Owing to the excellent physical and chemical performance of lead(II) compounds, investigations on them are still of enormous signicance, before other substitutes are developed, the application of which may lead to the toxic metal pollution, though. There is a need for exploiting the unique coordination chemistry of Pb(II) for the development of practical ligands as extractants, lead-poisoning treatment agents and sensors as well as energetic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation